Answer:
[tex](a)\[/tex] [tex]18x^2 - 39x + 18 = 3(3x -2)(2x - 3)[/tex]
(b) See Explanation
Step-by-step explanation:
Given
[tex]18x^2 - 39x + 18[/tex]
Solving (a): Factorize Completely
[tex]18x^2 - 39x + 18[/tex]
Factor out the common term
[tex]18x^2 - 39x + 18 = 3(6x^2 - 13x + 6)[/tex]
Expand
[tex]18x^2 - 39x + 18 = 3(6x^2 - 9x -4x + 6)[/tex]
Factorize
[tex]18x^2 - 39x + 18 = 3(3x(2x - 3) -2(2x - 3))[/tex]
Factor out 2x - 3
[tex]18x^2 - 39x + 18 = 3(3x -2)(2x - 3)[/tex]
Solving (b): Verify the result
To do this, we simply multiply the terms of the polynomial
[tex]3(3x -2)(2x - 3)[/tex]
[tex]3(3x -2)(2x - 3) = (9x - 6)(2x - 3)[/tex]
Open brackets
[tex]3(3x -2)(2x - 3) = 18x^2 - 27x - 12x + 18[/tex]
[tex]3(3x -2)(2x - 3) = 18x^2 - 39x + 18[/tex]